2022
DOI: 10.1109/jsen.2021.3130953
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Film PZT-Based Multi-Channel Acoustic MEMS Transducer for Cochlear Implant Applications

Abstract: This paper presents a multi-channel acoustic transducer that works within the audible frequency range (250-5500 Hz) and mimics the operation of the cochlea by filtering incoming sound. The transducer is composed of eight thin film piezoelectric cantilever beams with different resonance frequencies. The transducer is well suited to be implanted in middle ear cavity with an active volume of 5 mm × 5 mm × 0.62 mm and mass of 4.8 mg. Resonance frequencies and piezoelectric outputs of the beams are modeled with Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Correlations between the input and output waveforms of the speech test also demonstrated that this approach could overcome the bottlenecks of the middle ear implantable sound detectors. [ 18 ] The sound detector presented in this study comprises the previous studies` outcomes and accommodates surgical operation methods. Available space in the middle ear could not be entirely utilized due to tissues, passing nerves, and long‐term patient health.…”
Section: Design and Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between the input and output waveforms of the speech test also demonstrated that this approach could overcome the bottlenecks of the middle ear implantable sound detectors. [ 18 ] The sound detector presented in this study comprises the previous studies` outcomes and accommodates surgical operation methods. Available space in the middle ear could not be entirely utilized due to tissues, passing nerves, and long‐term patient health.…”
Section: Design and Experimental Sectionmentioning
confidence: 99%
“…Our group has proposed a challenging approach to the self‐powered fully implantable cochlear implant concept. This concept, FLAMENCO: A Fully‐Implantable MEMS‐Based Autonomous Cochlear Implant, includes a multi‐channel acoustic transducer, [ 18 , 19 , 20 ] a piezoelectric energy harvester, [ 21 , 22 ] an interface circuit, [ 23 ] and a commercial cochlear electrode. [ 24 , 25 ] To comply with the FICI standards, the entire system can be implanted inside the middle ear cavity, collect the ambient sound by using the natural hearing mechanism, and filter the signal into frequency bands to stimulate the auditory nerves ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Yüksel et al presented a similar device that worked in a bandwidth between 0.2 and 5.5 kHz, with dimensions of 5 × 5 × 0.62 mm 3 ( Figure 7 ). Tests were only carried out on a testbench in the laboratory [ 65 ].…”
Section: Sensing Devices In Healthcarementioning
confidence: 99%
“…The piezoelectric cantilever beams are critical in designing intelligent systems [1][2][3] as the primary structure of sensors. The cantilever beam structures [4], characterized by wide operating bandwidth, lightweight, powerful driving force, and high electromechanical conversion efficiency, have been used in the fields of micrometer/nanomechanical systems [5][6][7], server hard disk failure detection [8,9] and controller model validation [10,11].…”
Section: Introductionmentioning
confidence: 99%